Modulation of Zinc Homeostasis in Acanthamoeba castellanii as a Possible Antifungal Strategy against Cryptococcus gattii - Ribeiro, Nicole S.; dos Santos, Francine M.; Garcia, Ane W. A.; Ferrareze, Patrícia A. G.; Fabres, Laura F.; Schrank, Augusto; Kmetzsch, Livia; Rott, Marilise B.; Vainstein, Marilene H.; Staats, Charley C. (Frontiers in Microbiology, 2017)
Cryptococcus gattii is a basidiomycetous yeast that can be found in the environment and is one of the agents of cryptococcosis, a life-threatening disease. During its life cycle, cryptococcal cells take hold inside environmental predators such as amoebae. Despite their evolutionary distance, macrophages and amoebae share conserved similar steps of phagocytosis and microbial killing. To evaluate whether amoebae also share other antifungal strategies developed by macrophages, we investigated nutritional immunity against cryptococcal cells. We focused on zinc homeostasis modulation in Acanthamoeba castellanii infected with C. gattii. The intracellular proliferation rate (IPR) in amoebae was determined using C. gattii R265 and mutants for the ZIP1 gene, which displays defects of growth in zinc-limiting conditions. We detected a reduced IPR in cells lacking the ZIP1 gene compared to wild-type strains, suggesting that amoebae produce a low zinc environment to engulfed cells. Furthermore, flow cytometry analysis employing the zinc probe Zinpyr-1 confirmed the reduced concentration of zinc in cryptococcal-infected amoebae. qRT-PCR analysis of zinc transporter-coding genes suggests that zinc export by members of the ZnT family would be involved in the reduced intracellular zinc concentration. These results indicate that amoebae may use nutritional immunity to reduce fungal cell proliferation by reducing zinc availability for the pathogen.